AdS amplitudes as CFT correlators - Máximo Bañados; Ernesto Bianchi; Iván Muñoz; Kostas Skenderis (Journal of High Energy Physics)
Abstract We show that AdS amplitudes are CFT correlators to all orders in the loop expansion by showing that they obey the conformal Ward identities. In particular, we provide explicit formulas for the constants and functions of cross-ratios that determine the CFT correlators in terms of bulk data.